Handmade leather bags & accessories - Ho, Elean (Design Originals, an imprint of Fox Chapel Publishing, 2011)
"Learn the art of creating elegant accessories from genuine leather with this inspiring guide. Handmade Leather Bags & Accessories shows how to make classic handbags and accessories with a decidedly modern flair. Gifted fashion designer Ho Yi Lun shares 28 simple strategies for enhancing any wardrobe with high-end luxuries without the high-end price tag. Even novice leatherworkers will be surprised at how much fun it is to make durable and sophisticated bags using these basic techniques. Gorgeous photographs, step-by-step diagrams, and easy-to-follow instructions make it easy. Readers can create a chic purse or shoulder bag to go with every outfit, and will find fresh and fabulous ideas for satchels, hobos, messenger bags and totes. The author shows how to make chic and urbane accessories for every taste, including iPad holders, business card cases, coasters, key ring tabs and much more"--